Lifestyle and risk factors associated with elevated prostate-specific antigen levels in rural men: implications for health counseling - Hsieh, Kun-Lu; Chang, Chia-Hao; Lin, Yu-Chih; Huang, Tung-Jung; Chen, Mei-Yen (Frontiers in Oncology, 2024)
BackgroundThe use of prostate-specific antigen (PSA) for early detection of prostate cancer (PCa) is common but controversial. In rural areas, PSA is widely used for screening because it is convenient and early-stage PCa often shows no symptoms. Studies suggest that PSA levels are linked to factors like unhealthy lifestyles, obesity, lack of exercise, inflammation, and aging. Proper use and interpretation of PSA are crucial for healthcare providers, especially in primary care settings. This study aims to explore the prevalence and factors linked to higher PSA levels in rural men.MethodsWe conducted a community-based cross-sectional study from March to December 2023 in the western coastal region of Taiwan. Men aged 40-75 years participated, completing a lifestyle questionnaire and providing blood samples for cardiometabolic biomarkers and PSA levels. PSA levels of ≥ 4.0 ng/mL were considered elevated. We used propensity score matching (PSM) and genetic matching (GM) for analysis, followed by regression analysis.ResultsIn total, 3347 male adults with a mean age of 56.3 years (SD=11.8, range 40-75), and without cancer-related diseases, were enrolled. Findings indicated that 3.9% (n=130) of men aged 40-75 years had a PSA ≥ 4 ng/mL. and many of them did not adopt health-related behaviors, including inadequate servings of vegetables, water intake, and engaging in regular exercise. Furthermore, more than half of the participants had high blood pressure, and over one-quarter exhibited a higher waist-hip ratio and cardiometabolic diseases. After employing propensity score matching (PSM) and genetic matching (GM) with respect to age and education, the multivariate logistic regression model indicated that less water intake (p<0.01), higher waist-hip ratio (> 0.95) (p<0.05), and being diagnosed with cardiometabolic diseases (p<0.05) were significantly associated with a higher serum PSA level.ConclusionThis study revealed that inadequate water intake and obesity related diseases are significant risk factors associated with elevated PSA levels among male adults living in rural areas. It is important for frontline healthcare providers to carefully interpret the meaning of a high PSA level. Additionally, launching a longitudinal study is necessary to further investigate its relation to PCa.